Nepal Health Research Council Paves Path to Ethical Research Processes - Neupane, Sunisha; Sinha, Chaitali (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
This case study outlines an ethics approval process experienced during a maternal health research project in Nepal. The Government of Nepal established the Nepal Health Research Council (NHRC) in 1991, along with the Scientific and Ethics Committee reviewing health related research. However, not all researchers apply for ethics approval. Although researchers may claim a lack of clarity on the kinds of research studies needing approval, the authors argue that the guidelines are sufficiently clear if explored and duly followed. The inconsistencies in seeking ethics approval from NHRC could simply mean that researchers are not aware of this ethical review process. Perhaps the guidelines are not strictly enforced. Nevertheless, as researchers it is our responsibility to seek ethical approval as a matter of principle, without considering it a barrier to research.